PERANAN KEKUATAN RELATIT OTOT UNTUK BELAJAR JUDO - Jumhan Pida (Universitas Negeri Yogyakarta, 1999)
The research is meant to find out the role of muscle's relative strength in judo learning.The method used is descriptive correlation method with path analysis. technique. Cousal models being hypothesized correlate the wi